Pengajaran Kosakata Dasar Bahasa Inggris (English Basic Vocabulary) dengan Metode Drilling di SMPN Satu Atap 1 Jabiren Raya - Marcelina Marcelina; Sabarun; Nurul Wahdah; Herawati (Cv. Utility Project Solution, 2022)
To develop the ability to remember English vocabulary, this community service activity aims to educate and introduce English vocabulary with the drilling method. The method for doing community service is through demonstrations. The drilling or repetition method is used to teach English vocabulary during the implementation of this activity. Several steps must be taken, including scheduling foreign language vocabulary, especially for English, presenting English vocabulary materials, using English vocabulary in context, inviting students to interpret or define each new word taught, repeating English vocabulary materials, and providing tests to measure how well students learn English vocabulary using drilling methods. Students need to love learning so that they can gain vocabulary quickly and be motivated to maintain English. To make effective use of it, students must also be able to manage their time by using various drilling methods, which will keep them engaged and excited in learning their English. The educator's task in this situation is to select and implement an English vocabulary teaching strategy suitable for junior high school.